Use of Synchrotron Phase-Sensitive Imaging for the Investigation of Magnetopriming and Solar UV-Exclusion Impact on Soybean (Glycine max) Leaves - Fatima, Anis (Cells, 2021)
The combined response of exclusion of solar ultraviolet radiation (UV-A+B and UV-B) and static magnetic field (SMF) pre-treatment of 200 mT for 1 h were studied on soybean (Glycine max) leaves using synchrotron imaging. The seeds of soybean with and without SMF pre-treatment were sown in nursery bags kept in iron meshes where UV-A+B (280–400 nm) and UV-B (280–315 nm) from solar radiation were filtered through a polyester filters. Two controls were planned, one with polythene filter controls (FC)- which allows all the UV (280–400 nm); the other control had no filter used (open control-OC). Midrib regions of the intact third trifoliate leaves were imaged using the phase-contrast imaging technique at BL-4, Indus-2 synchrotron radiation source. The solar UV exclusion results suggest that ambient UV caused a reduction in leaf growth which ultimately reduced the photosynthesis in soybean seedlings, while SMF treatment caused enhancement of leaf growth along with photosynthesis even under the presence of ambient UV-B stress. The width of midrib and second-order veins, length of the second-order veins, leaf vein density, and the density of third-order veins obtained from the quantitative image analysis showed an enhancement in the leaves of plants that emerged from SMF pre-treated seeds as compared to untreated ones grown in open control and filter control conditions (in the presence of ambient UV stress). SMF pre-treated seeds along with UV-A+B and UV-B exclusion also showed significant enhancements in leaf parameters as compared to the UV excluded untreated leaves. Our results suggested that SMF-pretreatment of seeds diminishes the ambient UV-induced adverse effects on soybean.